THE EFFECTS OF TEACHING METHOD AND EMOTIONAL INTELLIGENCE UPON STUDENTS SPEAKING SKILL AT SMAN 1 KOTO KAMPAR HULU - Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2017)
This study aims to determine the effects of teaching method and emotional intelligence upon students speaking skill at SMAN 1 Koto Kampar Hulu. Research hypothesis included: 1) there is effect of teaching method upon students speaking skill, 2) there is effect emotional intelligence upon students speaking skill, 3), there is interaction between teaching method and emotional intelligence upon students speaking skill. Method used in this research in experimental method. The population is all students and the sample of 40 students who obtained a random sampling technique that use cluster sampling. Instrument that is used is result test of students speaking skill in the multiple choice with 35 items that is tested validity with reliability coefisient = 0,82, questionnaire 38 items of emotional intelligence that is tested validity with reliability coefficient = 0, 72. Analysis of data uses analysis of variance (ANOVA) two-ways. Result of the rsearch show that there sre effects of teaching method and emotional intelligence upon studnts speaking skill.